Syllable-first rather than letter-first to improve phonemic awareness - Maria Vazeux (Nature Portfolio, 2020)
Abstract The present study investigates the nature of the spelling-to-sound correspondences taught to enhance phonemic awareness in prereaders. The main assumption in the literature is that learning the alphabetic code through letter-to-phoneme correspondences is the best way to improve phonemic awareness. The alternative syllabic bridge hypothesis, based on the saliency and early availability of syllables, assumes that learning to associate letters to phonological syllables enables phoneme units to be the mirror of the letters and to become accessible, thereby developing phonemic awareness of prereaders. A total of 222 French-speaking prereaders took part in a 4-session learning program based on correspondences either between letters and syllables (letters-to-syllable group) or between letters and phonemes (letter-to-phoneme group), and the fifth last session on coding and decoding. Our results showed a greater increase in phonemic awareness in the letters-to-syllable group than in the letter-to-phoneme group. The present study suggests that teaching prereaders letters-to-syllable correspondences is a key to successful reading.